The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1097/00007890-199605150-00016
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Late Deaths After Liver Transplantation

Abstract: Late deaths (after more than 1 year) after liver transplantation were analyzed in a series of 464 consecutive patients who received liver grafts between 1982 and 1993. Recipients who survived the first posttransplant year (n = 365) had actuarial 5- and 10-year survival rates of 92% and 84%, respectively. Thirty-five patients died between 1.1 and 7.6 years after transplantation (mean, 3.2 +/- 1.9 years). The most common causes of death were related to immunosuppression (40%), namely, chronic rejection, opportun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
49
1
4

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(61 citation statements)
references
References 22 publications
7
49
1
4
Order By: Relevance
“…13 The somatic symptoms that we found (excess appetite, trembling, and headaches) can be considered to be the side effects of immunosuppressive drugs. It was reported that deaths related to immunosuppressive treatments from chronic rejection, opportunist infections, and lymphoma represent 40% of late mortality after LT. 23 Pinson et al 24 are convinced that results of the QOL can be used similarly to the rate of rejection to determine immunosuppression regimen or other strategies of patient management. During recent years, a dramatic improvement has been achieved in the area of electronic data transmission.…”
Section: Discussionmentioning
confidence: 99%
“…13 The somatic symptoms that we found (excess appetite, trembling, and headaches) can be considered to be the side effects of immunosuppressive drugs. It was reported that deaths related to immunosuppressive treatments from chronic rejection, opportunist infections, and lymphoma represent 40% of late mortality after LT. 23 Pinson et al 24 are convinced that results of the QOL can be used similarly to the rate of rejection to determine immunosuppression regimen or other strategies of patient management. During recent years, a dramatic improvement has been achieved in the area of electronic data transmission.…”
Section: Discussionmentioning
confidence: 99%
“…However, they may still jeopardize the graft, resulting in graft loss in approximately 1% to 3% of transplant recipients. 5,11,12 …”
Section: Frequency Of Biliary Complicationsmentioning
confidence: 99%
“…1,2 As long-term liver transplant survival improves, cardiovascular complications are emerging as a major cause of both morbidity and mortality. In an early retrospective analysis of late deaths after liver transplantation, Asfar et al 3 found that of 365 patients who survived the first transplant year (from an original cohort of 465 consecutive patients), 35 patients died between 1.1 and 7.6 years after transplantation. Five of these late deaths (14%) were from cardiovascular disease, representing the third most common cause of late mortality, after recurrence of the primary liver disease and complications of immunosuppression.…”
Section: Atherosclerotic Disease In Liver Transplant Recipientsmentioning
confidence: 99%